2021
DOI: 10.3389/fimmu.2021.790658
|View full text |Cite
|
Sign up to set email alerts
|

Immune Metabolism of IL-4-Activated B Cells and Th2 Cells in the Context of Allergic Diseases

Abstract: Over the last decades, the frequency of allergic disorders has steadily increased. Immunologically, allergies are caused by abnormal immune responses directed against otherwise harmless antigens derived from our environment. Two of the main cell types driving allergic sensitization and inflammation are IgE-producing plasma cells and Th2 cells. The acute activation of T and B cells, their differentiation into effector cells, as well as the formation of immunological memory are paralleled by distinct changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Hence, in the following study, we identified the DEGs in CD4+ T cells between AR patients and healthy individuals. Then, GO analysis was performed, and the results showed that AR-related DEGs were closely associated with cytological functions such as T cell activation and differentiation, which contribute to the regulation of immune metabolism and release of cytokines in allergic diseases ( 56 ). Then we assessed cell subtypes in the immune-infiltrating microenvironment from CSU samples.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in the following study, we identified the DEGs in CD4+ T cells between AR patients and healthy individuals. Then, GO analysis was performed, and the results showed that AR-related DEGs were closely associated with cytological functions such as T cell activation and differentiation, which contribute to the regulation of immune metabolism and release of cytokines in allergic diseases ( 56 ). Then we assessed cell subtypes in the immune-infiltrating microenvironment from CSU samples.…”
Section: Discussionmentioning
confidence: 99%
“…The possible factors for these differences are as follows: firstly, antigen-specific T and B cells are activated in PA, MA, and Different levels of sIgE and sIgG1 were found in this study, which may reflect the different metabolisms of T and B cells and contribute to DALs. [75,76] Secondly, different microbiota composition caused by different FAs may be another contributing factor. [77] Interactions between microbiota and immune cell subsets in the gut might contribute to dysregulated lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a typical proinflammatory cytokine that is implicated in many inflammatory conditions, including allergic and autoinflammatory disorders such as AD, bronchial asthma, and contact hypersensitivity [ 50 ]. IL-4 is crucial in the development of allergic disorders because of its influence over T helper cell development and production of IgE [ 51 ]. IL-4 also promotes the expression of IL-5, which is a cytokine responsible for maturation and release of eosinophils [ 52 ].…”
Section: Discussionmentioning
confidence: 99%